Simulation of nitrogen losses from flooded rice fields using wind tunnel experiment / Kamaruzaman Wan Yusof ... [et al.] - Wan Yusof, Kamaruzaman; Bouwmeester, Reinier; Ahmad, Hamidon; Hamzah, Siti Hawa; Hassan, Ruslan; Saufian, Mohd Fauzi (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
A research has been done to study the effect of wind on fertilizer losses from rice paddies. The main aim of the study was to identify the major parameters influencing the process of ammonia (NHJ volatilization from the water surface in a microplot. The study was conducted employing a construction of a 15.6 metre long test section of a wind tunnel with 1.0 metre square cross section. Ammonia concentration experiments were carried out to determine the amount of ammonia that evaporated into the atmosphere. The tests were performed in Civil Engineering laboratory of Institut Teknologi MARA, Shah Alam, using the wind tunnel with 0.25 metre deep and 1 metre wide water channel as a prototype rice-paddy-field condition.